Penerapan Bauran Pemasaran Syariah Pada Produk KPR BTN Syariah Kantor Cabang Surabaya - Sopyan Khoerudin; Muhammad Fajrul Falah; Saputro, Noven Lukito Hadi (ITB AAS INDONESIA Surakarta, 2025)
The purpose of this study is to explore the application of Sharia marketing mix in the KPR (mortgage) BTN Syariah product in Surabaya. Utilizing a qualitative approach based on Grounded Theory, this research aims to develop a new theory regarding social interaction within the context of Sharia marketing. The findings indicate that the KPR BTN Syariah product, which is free from usury contracts, consists of two main categories: platinum and subsidy. Pricing is determined transparently, involving developers and the government, while avoiding hoarding and price manipulation practices. Promotion is carried out through various media and consumer education regarding the differences between Sharia and conventional mortgages. The transparent and professional service process, along with convincing physical evidence, contributes to consumer trust. The conclusion of this study emphasizes that KPR BTN Syariah not only adheres to Sharia principles but is also acceptable to a broader society, including non-Muslims, by upholding values of honesty, professionalism, and trustworthiness.